A prospective study of the impact of AGTR1 A1166C on the effects of candesartan in patients with heart failure. (May 2018) - de Denus, Simon; Dubé, Marie-Pierre; Fouodjio, René; Huynh, Thao; LeBlanc, Marie-Hélène; Lepage, Serge; Sheppard, Richard; Giannetti, Nadia; Lavoie, Joël; Mansour, Asmaa; Provost, Sylvie; Normand, Valérie; et al.
Aim: To evaluate the impact of AGTR1 A1166C (rs5186) on the response to candesartan in patients with heart failure.Materials & methods: Prospective, multicentre, open-label study. We studied 299 symptomatic patients with heart failure presenting a left ventricular ejection fraction ≤40%.Results: Reductions in the primary end points of natriuretic peptides were not significantly associated with AGTR1 A1166C. Nevertheless, carrying the 1166C allele was associated with a greater compensatory increase in renin activity (p = 0.037) after 16 weeks of treatment with candesartan and a more modest effect on aldosterone concentrations (p = 0.022).Conclusion: AGTR1 1166C carriers may experience a greater long-term compensatory renin–angiotensin–aldosterone system activation following treatment with candesartan. Whether these associations ultimately influence clinical outcomes requires investigation. Clinicaltrials.gov : NCT00400582